О некоторых результатах подготовки и проведения финального турнира чемпионата европы по футболу 2012 года для экономики Украины - Бакуменко, М.А. (Культура народов Причерноморья, 2013)
Статья посвящена анализу результатов подготовки и проведения финального турнира
Чемпионата Европы по футболу 2012 года (Евро-2012) для экономики Украины и уровня ее
конкурентоспособности. Проведено соответствие ожидаемых результатов подготовки и проведения
Евро-2012 с функциями государственных реальных инвестиционных проектов. Сделан вывод о
положительном влиянии Евро-2012 на экономику Украины и ее конкурентоспособность в глобальном
мировом пространстве. Стаття присвячена аналізу результатів підготовки та проведення фінального турніру
Чемпіонату Європи з футболу 2012 року (Євро-2012) для економіки України та рівня її
конкурентоспроможності. Проведено відповідність результатів підготовки та проведення Євро-2012,
що очікувались, з функціями державних реальних інвестиційних проектів. Зроблено висновок про
позитивний вплив Євро-2012 на економіку України та її конкурентоспроможність у глобальному
світовому просторі. The article analyses the impact of preparation to and holding of the final tournament of the European
Football Championship 2012 (EURO 2012) on Ukraine’s economy and its competitive ratio globally. It gives
correlation of expected results from preparation to and holding of EURO 2012, defined in the State Target
Programme, to the functions of real investment projects: protective, budget, image, strategic and social ones.
The article analyses the actual results of EURO 2012 projects implementation, as well as the Championship’s
impact on Ukraine’s image. Also, it compares Ukraine’s competitiveness in 2012-2013 versus 2008-2009 in
terms of the 12 pillars of the Global Competitiveness Index (GCI), annually calculated by the World Economic
Forum. The author analyses the absolute increase and the rate of increase of GCI pillars in 2012-2013 (as
compared with 2008-2009) for Ukraine and a hypothetic economic system characterized by Innovation-driven
stage of development. To calculate the parameters of the above economic system, the author finds arithmetical
average of each of the 12 GCI pillars for 35 countries/economies referred to as Innovation-driven by the World
Economic Forum in 2012-2013. The preparation to and holding of EURO 2012 did not improve the 11th and 12th
GCI pillars (“Business sophistication”, “Innovation”), but promoted stabilization of their values. The author
analyses the dynamics of the gap between GCI pillars of the Innovation-driven economic system and those of
Ukraine in 2008-2009 and 2012-2013, and concludes that EURO 2012 projects had a positive impact on
Ukraine’s economy and its competitiveness.